The role of exopolysaccharide-producing cultures and whey protein ingredients in yoghurt. (October 2016) - Buldo, Patrizia; Benfeldt, Connie; Folkenberg, Ditte Marie; Jensen, Hanne Bak; Amigo, Jose Manuel; Sieuwerts, Sander; Thygesen, Katrine; van den Berg, Frans; Ipsen, Richard
Abstract: Physical stability and textural properties of eighteen low fat stirred yoghurts, differing in type of added dairy protein ingredients and in exopolysaccharide (EPS)-producing cultures, were studied by instrumental and sensorial measurements. Image analysis was performed to quantify the amount of grains and the amount of EPS. Enhanced textural properties and physical stability was observed in systems containing whey protein concentrate or particulated whey proteins as well as EPS-producing cultures. Irrespective of the culture used, casein and fractionated whey protein did not contribute to the textural properties. Sensory analysis confirmed the results obtained by instrumental measurements. Oral gel firmness was highly correlated to G′, viscosity at low shear rate, and instrumental measured firmness (R ≈ 0.82). Mouth thickness was well described by viscosity at high shear rate (R = 0.81), as well as by the hysteresis loop area and ropiness (R ≈ 0.81). Measured syneresis showed a significant relationship with visually evaluated syneresis (R = 0.76), and the amount of grains also correlated with visual evaluated graininess (R ≈ 0.81). The effect of the cultures on the sensory properties was revealed by multilevel simultaneous component analysis (MLSCA-P). Highlights: EPS must interact with milk proteins in order to enhance the textural properties. Interaction between EPS and protein aggregates decreased graininess. Sensorial measurements correlated well with instrumental measurements. MSCA-P showed to be a powerful tool to separate the contribution of the variables.